MODERATOR TO FUEL RATIO AND URANIUM FRACTION ANALYSIS OF SQUARE LATTICE MOLTEN SALT TRANSATOMIC POWER - B., Dion Bagus Nugraha; Harto, Andang Widi; Sihana (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2017)
Molten Salt Reactor Transatomic Power (MSR TAP) is a further development of the nuclear reactor Generation IV Reactor Molten Salt Reactor (MSR). MSR TAP generates clean electric power. It has a passive safety, resistance to proliferation, and low cost. MSR TAP can consume the rest of the nuclear fuel/spent nuclear fuel (SNF) of a commercial Light Water Reactor (LWR) fuel or use the main fuel, a salt solution UF4 - LiF - BeF2. MSR TAP uses Zirconium Hydride material for the moderator. This research has a purpose to determine the optimal size of uranium mole fraction on fuel and moderator radius from core design in order to produce optimum enrichment with the value 1 < keff <1.0065 using MCNP5 program. On the other hand, this research also aims to look for the optimum enrichment, which have inherent safety characteristics with αVoid < 0. Variations were made including the changes in the geometry of the moderator radius with a variation of 0.5 cm, 1 cm, 1.5 cm, 2 cm, 2.5 cm, 3 cm, 3.5 cm, 4 cm, and 4.5 cm; and the changes in the fuel uranium molar UF4 - LiF - BeF2 with molar variation of 15%, 20%, 25% and 30%. The geometry of Transatomic Power (MSR TAP) of companies Transatomic Power Corporation was used. The results show that the optimum variation is the salt solution UF4 - LiF - BeF2 with 25 % uranium mole fraction, 2.6 % enrichment and moderator radius of 1.5 cm. The optimum variation gives the keff value of 1.00124 ± 0.00078. The optimum value of reactivity void coefficient is -0.0684. It indicates an inherently safe design.